Prospective comparison of conventional radiography, low-dose computed tomography and magnetic resonance imaging in monoclonal gammopathies - Minarik, Jiri; Krhovska, Petra; Hrbek, Jan; Pika, Tomas; Bacovsky, Jaroslav; Herman, Miroslav; Scudla, Vlastimil (Biomedical papers, 2016)
Aims: We carried out a prospective study in order to identify the best imaging approach for patients with newly diagnosed multiple myeloma (MM) and monoclonal gammopathy of undetermined significance (MGUS).Methods: We assessed the extent of myeloma bone disease (MBD) in 112 individuals - 84 patients with MM and 28 individuals with MGUS. For the detection of osteolytic involvement we used whole-body magnetic resonance imaging (WB-MRI), low-dose computed tomography (LD-CT) and conventional radiography (CR). Each method assessed the presence of osteolytic involvement, compressive fractures and extramedullary involvement in the following regions: skull, spine and chest, pelvis and humerus and femur. We compared the difference in the number and extent of osteolytic involvement, especially the findings in CR negative patients.Results: Conventional radiography showed no superiority in any of the evaluated regions, and failed in the detection of extramedullary massess and spine involvement. WB-MRI was best at imaging the spine including extramedullary involvement, however, detection of osteolytic lesions of the skull was limited in comparison with both CR and LD-CT. Both WB-MRI and LD-CT were comparable in imaging of lesions of pelvis, humerus, femur and the presence of extramedullary masses. LD-CT showed superiority in detection of skull lesions but lower sensitivity in spine compared to WB-MRI.Conclusions: Our results confirm that relying solely on CR in the diagnostics of MM is insufficient. We suggest that the most suitable method for primary assessment of osteolytic involvement in monoclonal gammopathies should include either whole-body MRI together with CR of the skull or, with an equivalent sensitivity, whole body LD-CT.
Keywords: multiple myeloma; monoclonal gammopathy of undetermined significance; imaging methods; conventional radiography; whole-body magnetic resonance; whole-body low-dose computed tomography